EFFECT OF ACCOUNTING CONSERVATISM AND EARNINGS MANAGEMENT ON FIRM VALUES - Puteri Sarah Mutia (JASS (Journal of Accounting for Sustainable Society), 2022)
This study investigates how accounting conservatism and eaarnings management affect the value of a company. This research investigates state-owned firms that were listed on the Indonesia Stock Exchange between 2019 and 2021. The valuation of a company is determined using Tobin's Q formula. On the basis of incurred items, accounting conservatism is evaluated. Earnings management is evaluated using a modified version of the Jones model to determine the value of discretionary accruals. The samples were collected using a strategy of purposive sampling based on the author's criteria. Then, thirteen firms were collected for study. Therefore, this analysis utilizes 39 data samples. The research data were analyzed using SPSS 25. This study's findings demonstrate that (1) accounting conservatism impacts firm value, whereas (2) earnings management has no impact on firm value.